Commodifying learning? Ethical communication violations and professional boundaries of Indonesian influencer lecturers on social media - Robby Aditya Putra; Dete Konggoro; Maulida Fitri; Osman Koroglu (Kuras Institute, 2026)
Purpose − This study explores the phenomenon of the commodification of learning by influencer lecturers in Indonesia using social media. The main objective of this study is to analyze how lecturers’ practices in sharing content on social media can trigger ethical communication violations, blur professional boundaries, and affect students’ learning experiences as well as the protection of their rights in the digital era. Method − This study adopts a qualitative research design to examine the phenomenon of influencer lecturers in Indonesia, focusing on the commodification of learning, ethical communication violations, and professional boundaries on social media. Data was collected through a literature review and digital observation of lecturers’ activities on platforms such as Instagram, TikTok, and YouTube during the period from 2022 to 2025. A purposive sampling technique was used to select lecturers who actively produce educational content and demonstrate significant audience engagement. The research data consists of publicly available posts, videos, captions, and interactions, which were analyzed using iterative thematic analysis. The main themes identified include the commodification of learning, ethical communication violations and the blurring of professional boundaries. Ethical considerations were maintained by anonymizing all observed accounts. The analysis of this study is based on the Source Credibility Model, Kantian communication ethics, and professional Stephen J. Ball’s concept of performance. Findings − The findings reveal that the commodification practices of influencer lecturers are concretely manifested through packaging students’ expressions, emotions, and interactions as digital content oriented toward attention. This condition reduces the fundamental values of education. As a result, the use of social media by influencer lecturers not only has the potential, but clearly leads to violations of communication ethics, blurred professional boundaries, and a decline in academic credibility. This study emphasizes the urgent need for a clear separation between the role of lecturers as educators and as public figures. Influencer lecturers are required to consciously establish, internalize, and maintain clear ethical boundaries to uphold professionalism and academic integrity.